Être dansé - Lydia Zeghmar (Ateliers d'Anthropologie)
In Turkey’s Aegean hinterland, the musical and choreographic repertoire of the zeybek celebrates the heroism of maquis rebels of the Ottoman period, the efe. In this contribution, I analyse a particular moment in the zeybek danced performance called the “stroll”. Before fully entering into the dance, the soloist carries out an improvised walk lasting a few dozen seconds, during which time he gets into harmony with the musicians and seeks the state of dance. To characterise this transitional moment, zeybek dancers stress the dancer’s soul and temperament. I describe the various components of this start-up process used by the dancer, and clarify their meanings. We will study how the stroll contributes to sowing uncertainty as to the identity of the person who is danced, through the implementation of a liminality: between the walk and the dance, between the dancer as a person and the efe as a character.